Followership preferences for gender-based leadership behavioral characteristics in the virtual environment - Barth, Judith A., author; Geroy, Gary, advisor; Francis, James, committee member; Phillips, Dennis, committee member; Gilley, Ann, committee member (Colorado State University. Libraries, 2003)
The purpose of this study was to examine followership preferences for gender-based leadership behavioral characteristics in the virtual environment. A thorough literature review encompassing leadership, followership, and the virtual environment, found no clear answer to either of the research questions. As a result of the literature review, two null hypotheses were tested: 1. In the virtual environment, there is no relationship between any of the five followership types by gender and preference for gender-based leadership behavioral characteristics. 2. There will be no difference in followers' preferred gender-based leadership behavioral characteristics, as identified as predominantly male or female, when considered by followership type and gender. Through an on-line survey of professionals employed by Cooperative Extension in the western United States, original data was gathered on follower characteristics and preferences for leadership behavioral characteristics. Contrary to the followership distribution suggested by Kelley (1993), all but one of the Extension employees who chose to respond to the on-line survey fell in only one of the five followership types. This study found no significant relationship between any of the demographic characteristics: gender, work site, generation, location of clientele, or years of virtual work and a preference for male or female behavioral characteristics in the virtual environment. Finally, the results of this study provide additional evidence on the controversial issue of whether male and female leaders demonstrate significantly different leadership behaviors based solely on their gender. Respondents in this study failed to identify leadership behaviors as two dimensional, thus providing evidence that leadership behaviors are not gender-related. Rather the results of this study suggest that leadership as a characteristic has one major dimension not identified by gender. This study would support the hypothesis that there is no difference in the leadership behavioral characteristics of males and females, at least as perceived by followers in the virtual environment.
Keywords: gender differences; studies; research; behavior; software; success; communication; questionnaires; skills; personal computers; cooperation; participation; decision making; copyright; preferences; trust; females; critical thinking; personal relationships; males